Multimedia, computer graphics and broadcasting International Conference, MulGraB 2011, Held as Part of the Future Generation Information Technology Conference, FGIT 2011, in Conjunction with GDC 2011, Jeju Island, Korea, December 8-10, 2011. Proceedings, Part II - Kim, Tai-hoon (Communications in Computer and Information Science, 2011)
The two volume set, CCIS 262 and 263, constitutes the refereed proceedings of the International Conference, MulGraB 2011, held as Part of the Future Generation Information Technology Conference, FGIT 2011, in conjunction with GDC 2011, Jeju Island, Korea, in December 2011. The papers presented were carefully reviewed and selected from numerous submissions and focuse on the various aspects of multimedia, computer graphics and broadcasting.